CHARACTERIZATION OF NANO MINERALS WASTE OF KIJING SHELL (Pilsbryoconcha sp) FROM POOL AND RIVER - Manullang, Arkadius; Leksono, Tjipto; Iriani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract This research aims to obtain mussel shell nano minerals (Pilsbryoconcha sp) from ponds and rivers with the same treatment seen from physical, morphological and chemical parameters (mineral content). Physical analysis parameters observed were the calculation of yield and degree of whiteness of nano minerals. Morphological parameters observed were SEM and particle size. The same extraction of the two mussel shells was carried out with two treatments with the criteria for the appearance of the color of the nano minerals produced in yellow and slightly white. The highest yield resulting from the same extraction was found in pond mussel shells. The mineral content found in the mussel shell nano minerals has the highest percentage of calcium minerals, with a scale of 100% the mussel shell nano minerals having a higher mineral component. Specifically, the nano mineral size obtained is around 573 nm with a magnification of 20,000x and for the greatest magnification of 40,000x, the nano mineral size is around 1420 nm. The mineral nano powder obtained was shaped like a crystal, and in general the results obtained showed that the crystals formed were of the type of vaterite. Keywords: Nano minerals, Pilsbryoconcha sp, SEM.